Humanitarian Logistics and Sustainability - Klumpp, Matthias; de Leeuw, Sander; Regattieri, Alberto; de Souza, Robert (Lecture Notes in Logistics, 2015)
This contributed volume combines conceptual and strategic research articles dealing with the "why" and "to what end" of sustainable operations in humanitarian logistics, as well as operational research contributions regarding the "how" from the United Nations as well as from researchers and organizations from different countries (Germany, Australia, Singapore, Italy, Denmark, Jordan). The target audience primarily comprises research experts, decision makers  and practitioners in the field, but the book may also be beneficial for graduate students.